1993
DOI: 10.5511/plantbiotechnology1984.10.38
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Somatic Embryogenesis in Carrot by Osmotic Stress.

Abstract: Segments of cotyledon and apical tip taken from 1-week-old seedlings of Daucus carota L. were cultured for 3 weeks on hormone-free Murashige and Skoog's (MS) medium containing high amounts of sucrose (0.3-0.7M) and then transferred to the same medium with lower sucrose concentration (0.09M). Somatic embryos were formed from the segments 3 to 6 weeks after the transfer. On the other hand, hypocotyl segments given the same treatment did not produce somatic embryos. When the primary culture medium contained 0.61M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 2 publications
1
46
1
Order By: Relevance
“…Karami et al (2008) reported the highest secondary somatic embryogenesis was observed when combination of sucrose and mannitol was added to the culture medium. Previous reports on regulation of osmotic pressure in culture medium by mannitol have been done by many researchers (Robert 1991;Kamada et al 1993;Ikeda-Iwai et al 2002). Therefore, it would be interesting to study the influence of sucrose combined with an osmotic agent such as mannitol and/or of a sequential supply of high concentration.…”
Section: Secondary Somatic Embryogenesismentioning
confidence: 99%
“…Karami et al (2008) reported the highest secondary somatic embryogenesis was observed when combination of sucrose and mannitol was added to the culture medium. Previous reports on regulation of osmotic pressure in culture medium by mannitol have been done by many researchers (Robert 1991;Kamada et al 1993;Ikeda-Iwai et al 2002). Therefore, it would be interesting to study the influence of sucrose combined with an osmotic agent such as mannitol and/or of a sequential supply of high concentration.…”
Section: Secondary Somatic Embryogenesismentioning
confidence: 99%
“…In carrot (Daucus carota), a model plant for SE, stress treatment on the PGR-free medium induces SE in the presence of different chemicals such as 0.7 M sucrose, 0.3 M NaCl or 0.6 mM CdCl Harada et al 1990;Kiyosue et al 1990;Kamada et al 1993).…”
Section: Stress and Somatic Embryogenesismentioning
confidence: 99%
“…3-A). [9][10][11][12]17]. These results indicate that these proteins may be directly related to induction of somatic embryogenic competence and/or early events of somatic embryo development prior to morphological differentiation of embryos rather than stress tolerance.…”
Section: Discussionmentioning
confidence: 80%
“…On the other hand, it has been reported that carrot somatic embryogenesis is induced by the treatments of apical tip segments with high concentrations of sucrose [8,9], NaCI [10] or heavy metal ions such as Cd2+ (Kiyosue et al, 1990) [11] in phytohormone-free medium. Futhermore, heat stress also induces somatic embryogenesis in phytohormone -free medium (Kamada et al, 1994) [12].…”
Section: Introductionmentioning
confidence: 99%